2021
DOI: 10.1371/journal.pone.0260650
|View full text |Cite
|
Sign up to set email alerts
|

Top-down proteomic identification of plasmid and host proteins produced by pathogenic Escherichia coli using MALDI-TOF-TOF tandem mass spectrometry

Abstract: Fourteen proteins produced by three pathogenic Escherichia coli strains were identified using antibiotic induction, MALDI-TOF-TOF tandem mass spectrometry (MS/MS) and top-down proteomic analysis using software developed in-house. Host proteins as well as plasmid proteins were identified. Mature, intact protein ions were fragmented by post-source decay (PSD), and prominent fragment ions resulted from the aspartic acid effect fragmentation mechanism wherein polypeptide backbone cleavage (PBC) occurs on the C-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…However, some recent studies have demonstrated that the noncovalent dissociation in the matrix‐assisted laser desorption/ionization (MALDI) process can be overcome by the use of appropriate matrix and chemical cross‐linking (Chen et al, 2016). The potential of MALDI combined with TDMS for proteomics studies has also been explored (Fagerquist & Dodd, 2021; Fagerquist & Sultan, 2011; Oros et al, 2020; Sturiale et al, 2011). Moreover, a laser ablation electrospray ionization (LAESI) was demonstrated for ionizing protein complexes in their native state (Kooijman et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, some recent studies have demonstrated that the noncovalent dissociation in the matrix‐assisted laser desorption/ionization (MALDI) process can be overcome by the use of appropriate matrix and chemical cross‐linking (Chen et al, 2016). The potential of MALDI combined with TDMS for proteomics studies has also been explored (Fagerquist & Dodd, 2021; Fagerquist & Sultan, 2011; Oros et al, 2020; Sturiale et al, 2011). Moreover, a laser ablation electrospray ionization (LAESI) was demonstrated for ionizing protein complexes in their native state (Kooijman et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…MALDI-ToF/ToF was used as an analytical tool for the determination of bacteria in urine samples collected from patients with urinary tract infections [ 108 ]. Furthermore, MALDI-ToF/ToF was successfully used for identification of full and truncated proteins produced by pathogenic Escherichia coli strains [ 140 ]. MALDI-ToF/ToF MS could aid in the generation of accurate molecular formulas and structural information to rapidly discriminate bacterial function [ 141 ] as well as for identification of new viral evasion strategies and fundamental factors governing host-microbial interactions as has been demonstrated in HPV infection that alters vaginal microbiome via downregulation of host mucosal innate peptides used by Lactobacilli as amino acid sources [ 142 ].…”
Section: Applications Of Maldi-ms/ms-based Proteomicsmentioning
confidence: 99%
“…Among those proteins, HdeA (monomer), HdeB (monomer), CspE and Hpr have previously been identified by MALDI top-down MS of cell lysates of various strains of E. coli . 25 HdeA, HdeB, YibT and YgiW were identified in a bottom-up LC-MS proteomics study of outer membrane vesicles obtained from a range of E. coli strains. 26 Acyl carrier protein has been identified in a bottom-up MALDI study.…”
mentioning
confidence: 99%